Boy - Ings, W (Room8, 2004)
Boy is Welby Ings' short film about a young male prostitute in a small New Zealand town who discovers the truth behind a fatal hit and run accident. When news of the death spreads through the district, the family of the responsible driver realise that the boy must be kept silent. Using local gossip they set out to frighten him into submission. The pressure becomes increasingly aggressive and through it the boy [who never speaks] battles to expose the truth. Boy was a multi-award winning experiment in poetic narrative as film. Between 2004 and 2007 it was officially selected in competition for over 50 international film festivals. It was also long-listed for the 2006 Academy awards after winning Best Short Film in the prestigious Cinequest International Film Festival. The film flows as a single, linear thread. Its aesthetic references stylistic approaches taken to advertising narratives in New Zealand [integrated colour palettes, editing rhythms and structures]. A significant feature of this approach is the highly condensed nature of the story. The narrative [which might normally be told as a 55 minute drama] is now heavily compressed into less than a quarter of that time. As a result edited sequences average out at 1.2 seconds in duration. The effect establishes an unusually condensed, dreamlike, visually rich form of storytelling that alludes to the world of music video and TVCs but uses these references to develop a very intricate, intensified form of storytelling. [35mm silent, short film with typography.]
Keywords: Narrative film poetry; Male prostitution; Short film; Spatio-temporal typography; Argot